A Web-Based Communication Aid for Patients with Cancer: The CONNECT™ Study - Meropol, Neal J. (2013)
BACKGROUND: Cancer patients and their oncologists often report differing perceptions of consultation discussions and discordant expectations regarding treatment outcomes. CONNECT™, a computer-based communication aid, was developed to improve communication between patients and oncologists. METHODS: CONNECT includes assessment of patient values, goals, and communication preferences; patient communication skills training; and a pre-consult physician summary report. CONNECT was tested in a three-arm, prospective, randomized clinical trial. Prior to the initial medical oncology consultation, adult patients with advanced cancer were randomized to (a) control; (b) CONNECT with physician summary, or (c) CONNECT without physician summary. Outcomes were assessed with post-consultation surveys. RESULTS: Of 743 patients randomized, 629 completed post-consultation surveys. Patients in the intervention arms (versus control) felt that the CONNECT program made treatment decisions easier to reach (p=0.003) and helped them to be more satisfied with these decisions (p<0.001). In addition, patients in the intervention arms reported higher levels of satisfaction with physician communication format (p=0.026) and discussion regarding support services (p=0.029) and quality of life concerns (p=0.042). The physician summary did not impact outcomes. Patients with higher levels of education and poorer physical functioning experienced greater benefit from CONNECT. CONCLUSION: This prospective randomized clinical trial demonstrates that computer-based communication skills training can positively affect patient satisfaction with communication and decision making. Measureable patient characteristics may be used to identify subgroups most likely to benefit from an intervention such as CONNECT.